The Critical Discourse Analysis of Content Pedagogy in The Indonesian EFL Textbook: The Alignment with Kurikulum Merdeka - Islamy, Firsty Twentieth Januar; Kristiawan, Dana Yudha; Rahman, Abd. (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to critically analyze the pedagogical representation in the Indonesian EFL textbook